#24: Death is Antibiotic-Microbiota Dependent in a Humanized Mouse Model of Late-Onset Neonatal Sepsis. (26th March 2021) - Schwartz, D; D'Souza, A; Crofts, T; Ning, J; Shalon, N; Robinson, J; Henderson, J; Warner, B; Tarr, P; Dantas, G
Abstract: Background: Premature infants receive antibiotics frequently for culture-negative sepsis, which diminishes gut microbial diversity and increases susceptibility to infections by antibiotic-resistant pathogens. Neonates with decreased gut microbiota diversity, termed dysbiotic, have dysregulated immune systems marked by increased concentrations of circulating activated T cells and decreased concentrations of circulating neutrophils and dendritic cells. We hypothesize that antibiotics (1) enrich for pathobionts within the gut, (2) promote a systemic, proinflammatory host response, and (3) cause death in an antibiotic specific manner in a gnotobiotic model of preterm gut microbiota development. Methods: We colonized germ-free (GF) dams and sires with stools from preterm infants. Mouse pups acquire this neonatal microbiota, and at 10 days of life (DOL), we treat them with clinically relevant doses of antibiotics subcutaneously for 3 days. We use metagenomic shotgun sequencing of individual pup fecal samples longitudinally to ascertain phylogenetic composition, and use flow cytometry and multiplex cytokine arrays to determine the local and peripheral immune response. Results: Using two representative microbiota from human neonates (hereafter referred to as microbiota A or B), we show that 94% of pups given microbiota A survive vs. 64% given microbiota B after meropenem/probenecid treatment (Figure 1; P < 0.05; n = 18–28 mice in > independent experiments). 40% of pups given microbiota A treated with ampicillin/gentamicin/probenecid survived (Figure 1; P < 0.01 relative to meropenem/probenecid or probenecid). Klebsiella species dominated the gut microbiota of microbiota A-humanized pups who succumbed and were found in the lung, liver, and spleen of one animal at necropsy. Enterococci dominated the gut microbiota of microbiota B-humanized pups who died during treatment. Pups colonized with microbiota B had increased peripheral CD4+ T cells at sacrifice after treatment compared with microbiota A-humanized pups (61% vs. 44% of circulating T cells, P < 0.0005). Conclusions: Our model of preterm microbiota development and perturbation by antibiotics demonstrates potential bacterial translocation, proinflammatory immune response, and death dependent on the microbiota–antibiotic combination. Our transgenerational humanized-microbiota mouse model can be utilized to determine antibiotic by microbiota perturbation and examine risks of late-onset sepsis from antimicrobials.